The influence of intersensory discrepancy on visuo-haptic integration is similar in 6-year-old children and adults - Jovanovic, Bianca; Drewing, Knut (Frontiers in Psychology, 2014)
When participants are given the opportunity to simultaneously feel an object and see it through a magnifying or reducing lens, adults estimate object size to be in-between visual and haptic size. Studies with young children, however, seem to demonstrate that their estimates are dominated by a single sense. In the present study, we examined whether this age difference observed in previous studies, can be accounted for by the large discrepancy between felt and seen size in the stimuli used in those studies. In addition, we studied the processes involved in combining the visual and haptic inputs. Adults and 6-year old children judged objects that were presented to vision, haptics or simultaneously to both senses. The seen object length was reduced or magnified by different lenses. In the condition inducing large intersensory discrepancies, children’s judgments in visuo-haptic conditions were almost dominated by vision, whereas adults weighted vision just by 40%. Neither the adults’ nor the children’s discrimination thresholds were predicted by models of visuo-haptic integration. With smaller discrepancies, the children’s visual weight approximated that of the adults and both the children’s and adults' discrimination thresholds were well predicted by an integration model, which assumes that both visual and haptic inputs contribute to each single judgment. We conclude that children integrate seemingly corresponding multisensory information in similar ways as adults do, but focus on a single sense, when information from different senses is strongly discrepant.